The Challenges of Cooperative Learning for Young Learners at the Junior High School Level - NAILA, NAJMI; Zea Jelika Dewanda; Nova Agus Mulia; Iis Hajijah; Selnistia Hidayani (Jurnal Intelek Insan Cendikia, 2025)
This study aims to investigate the challenges experienced by junior high school students in engaging with Cooperative Learning (CL) during English lessons. Using a descriptive qualitative approach with a participatory design, the researchers directly implemented CL in the classroom and observed student interactions. Data were collected from 20 seventh-grade students through open-ended questionnaires, group interviews, and classroom observations. The findings reveal that students generally have a positive perception of group learning, particularly in terms of motivation, comfort, and peer collaboration. However, several obstacles were identified, including unequal task distribution, difficulties in communication, inactive group members, and limited understanding of the material during group discussions. These challenges suggest that although CL offers emotional and social benefits, its implementation requires structured guidance and support to ensure equal participation and effective learning. The study implies that fostering active engagement and balanced collaboration among students is essential for maximizing the benefits of Cooperative Learning in junior high school contexts.